Analysis of Village Asset Management Based on Regulation of the Minister of Home Affairs Number 1 of 2016 (A Case Study at Lerepako Village, South Konawe Regency) - Azzahra Niikmatul Ilmi; Dewi Suci Muthiara Rachman; Abdul Azis Muthalib; Yusuf Jaya Saputra; Reyhan Dzikriansyah Suanrno (Jurnal Akuntansi Publik Nusantara, 2026)
This research aims to identify and analyze the village asset management process based on the Regulation of the Minister of Home Affairs Number 1 of 2016 in Lerepako Village, South Konawe Regency, and the factors causing the village asset management process to not run optimally. This research uses a qualitative descriptive method with data sourced from primary data in the form of interviews and secondary data through documentation. The results of this study indicate that the village asset management process in Lerepako Village, South Konawe Regency, can be considered good but not fully in accordance with the Regulation of the Minister of Home Affairs Number 1 of 2016 concerning Village Asset Management. The inhibiting factors for optimizing the village asset management process in Lerepako Village, South Konawe Regency, are due to the still inadequate competence of human resources, lack of communication about the implementation of village asset management regulations, some village assets lacking legal certainty of ownership, the implementers' non-compliance with village asset management regulations, as well as other parties unilaterally claiming land. Additionally, the expertise of activity managers in the village asset administration process and the organizational commitment have not been fully maximized.